NFL injuries before and after the 2011 Collective Bargaining Agreement (CBA) - Binney, Z. O.; Hammond, K. E.; Klein, M.; Goodman, M.; Janssens, C. J. W. (2018)
Introduction: The National Football Leagues (NFL) 2011 collective bargaining agreement(CBA) with its players placed a number of contact and quantity limitations on offseason, training camp, and regular season practices and workouts. Some coaches and others have expressed a concern that this has led to poor conditioning and a subsequent increase in injuries. Rigorous studies on the effects of the NFLs new practice restrictions have not been performed, however.Objective: We sought to assess whether the 2011 CBAs practice restrictions affected thenumber of overall, conditioning-dependent, and/or non-conditioning-dependent injuries inthe NFL or the number of games missed due to those injuries.Methods: The study population was player-seasons from 2007-2016 for any player who had participated in at least one career regular season game. We included only regular season, non-illness, non-head, game-loss injuries. Injuries were identified using a database from the website Football Outsiders based on public NFL injury reports and the injured reserve list. The primary outcomes were overall, conditioning-dependent and non-conditioning-dependent injury counts by season. We also investigated games missed due to these injuries as a secondary outcome. We calculated injury counts and games missed per season and compared the results before (2007-2010) and after (2011-2016) the CBA. We also used a Poisson interrupted timeseries model to assess whether there was an immediate change after the CBA or if a pre-CBA increase in injuries accelerated post-CBA.Results: The number of game-loss regular season, non-head, non-illness injuries grew from 701 in 2007 to 804 in 2016 (15% increase). The number of regular season weeks missed exhibited a similar increase. Conditioning-dependent injuries increased from 197 in 2007 to 271 in 2011 (38% rise), but were lower and remained relatively unchanged at 220-240 injuries per season thereafter. Non-conditioning injuries decreased by 37% in the first three years of the new CBA before returning to historic levels in 2014-2016. Poisson models forall, conditioning-dependent, and non-conditioning-dependent game-loss injury counts didnot show statistically significant detrimental changes associated with the CBA. Conclusions: We did not observe a sustained increase in conditioning- or non-conditioning-dependent injuries following the 2011 CBA. Other concurrent injury-related rule and regulation changes limit specific causal inferences about the practice restrictions, however, and further studies are warranted.